Penerapan Model Project Based Learning Untuk Meningkatkan Kemampuan Menulis Siswa Kelas VII Madrasah Tsanawiyah Nurul Huda Malang - Syamfa Agny Anggara (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2016)
Learning process has relationship with element infloence as approach, method, and technique. Intention of this research is describe, ( a) applying project based learning method for student class seventh of Arabic language in Madrasah Tsanawiyah Nurul Huda Malang, ( b) result improvement of writing arabic ability by project based learning method for student class VII in Madrasah Tsanawiyah Nurul Huda Malang. This Research use class action research. Result of this research indicate that applying of project based learning method can improve writing arabic ability for student class VII in Madrasah Tsanawiyah Nurul Huda Malang.